#81 : Result of Non-Invasive Preimplantation Genetic Testing for Aneuploidy in Different Culture Medium Condition - Pritta Ameilia Iffanolida; Achmad Kemal Harzif; Kresna Mutia; Ririn Rahmala Febri; Deka Putri Gunarwati; Mila Maidarti; Budi Wiweko; Andon Hestiantoro (Fertility & Reproduction, 2023)
Background and Aims: Non-invasive preimplantation genetic testing (niPGT-A) emerged from the discovery of embryonic DNA in spent embryo culture medium. Many studies have been developed in order to replace Preimplantation Genetic Testing (PGT) in assisted reproductive clinic, however the results between each study varies. We hypothesized that the condition of culture medium is one of the key factors that rely on. The aim of this study is to compare the niPGT-A result between single step culture medium (SCM) and two step culture medium (TCM). Method: We conducted a cross-sectional study to compare the niPGT-A result between SCM and TCM with tropectoderm (TE) biopsy performed on day 5/6 as a gold standard for chromosomal analysis. The embryo was individually cultured in a 20 uL volume of cuture medium, for SCM group we used Sage one step culture medium from D1 to D5. For TCM group we used Cleav culture medium from D1 to D3 followed by Blast medium until D5. In day 5/6 we performed TE biopsy, and the embryo was freezing, then we took the spent blastocyst medium (SBM). A total 240 samples of SCM, TCM and TE were screened for chromosomal abnormality by Next Generation Sequencing (NGS) method. Results: The amplification rate of SCM and TCM groups was both 100% with average DNA yield of 18.1 ng/uL and 25.2 ng/uL, respectively. We validated these results by comparing chromosome status of blastocyst stage embryos as the standard, SCM group have 98.4% sensitivity and 79.4% specificity meanwhile for TCM group chromosomal status assessment using SBM had sensitivity of 85% dan specificity of 70%. Conclusion: The results found report successful amplification, high agreement rates and good sensitivity and specificity of the culture medium analysis. We can conclude that the time the embryo remains in contact with the culture medium favored the results.